Strain-induced Stranski–Krastanov growth of Pd@Pt core–shell hexapods and octapods as electrocatalysts for methanol oxidation. Issue 31 (25th July 2017) - Xiong, Yalin; Ma, Yanling; Li, Junjie; Huang, Jingbo; Yan, Yucong; Zhang, Hui; Wu, Jianbo; Yang, Deren
Abstract : Pd@Pt core–shell hexapods and octapods were generated through the strain-induced Stranski–Krastanov growth mechanism and the hexapods exhibited the substantially enhanced catalytic properties towards methanol oxidation relative to the octapods and commercial Pt/C. Abstract : Bimetallic nanocrystals with a branched shape have received great interest as catalysts due to their unique structures and fascinating properties. However, the conventional synthetic approaches based on the island growth mode often lead to the dendritic nanostructures with inhomogeneous and uncontrolled branches. Here precise control over the number of branches has been realized in the deposition of Pt on Pd seeds through the Stranski–Krastanov growth mechanism. Based on such a growth mode, Pd@Pt core–shell hexapods and octapods have been generated by a seeded growth with Pd octahedra and cubes as the seeds, respectively. We found that Pt atoms are initially deposited on the side faces of Pd seeds through a layer-by-layer epitaxial growth in the presence of oleylamine (OAm), leading to a local strain focused at their corners. These strain-concentrated sites promote the subsequent island growth of Pt atoms at the corners of the Pd seeds, resulting in the Pd@Pt core–shell hexapods or octapods. Both the Pd@Pt core–shell hexapods and octapods exhibit the substantially enhanced catalytic properties in terms of activity and stability towards a methanol oxidation reaction (MOR) relative to the commercial Pt/C. Specifically, the Pd@Pt core–shell hexapods show the highest specific (1.97 mA cm −2 ) activity and mass activity (0.52 mA μgPt −1 ) for the MOR, which are 5.8 and 2.6 times higher than those of the commercial Pt/C, respectively. This enhancement can probably be attributed to their unique structures and the synergistic effect between Pt and Pd.